2007
DOI: 10.1007/s00339-007-4350-9
|View full text |Cite
|
Sign up to set email alerts
|

Microstructuring of diamond bulk by IR femtosecond laser pulses

Abstract: t.v. kononenko 1,u m. meier 2 m.s. komlenok 1 s.m. pimenov 1 v. romano 2 v.p. pashinin 1 v.i. konov 1

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
98
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(101 citation statements)
references
References 30 publications
3
98
0
Order By: Relevance
“…LIPSS have been already fabricated on diamond and morphologically investigated by other groups [13][14][15][16][17]. To our knowledge, only Kononenko et al [18] reported on optical transmission behaviour as a function of laser fluence for fs-laser-induced microstructures in bulk natural and CVD diamond. However, optical properties of fs-laser LIPSS on diamond surface have not been investigated or reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…LIPSS have been already fabricated on diamond and morphologically investigated by other groups [13][14][15][16][17]. To our knowledge, only Kononenko et al [18] reported on optical transmission behaviour as a function of laser fluence for fs-laser-induced microstructures in bulk natural and CVD diamond. However, optical properties of fs-laser LIPSS on diamond surface have not been investigated or reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…A good example of this is given in the paper by Sanner et al (N. Sanner et al, 2009), where the range of values quoted for the ablation threshold for fused silica is given as 2-12 J cm -2 . This range is by no means an anomaly or the widest range published, for example the value for natural diamond is given as 10-80 J cm -2 (T. V. Kononenko et al, 2008) where the value fluctuates widely across a specimen surface. The reason for the range in values can be explained by considering that there are a number of ways of measuring the thresholds and even defining them (N. Sanner et al, 2009), there are also differences in the exact composition of the materials used and their source, as well as differences in the experimental set-up.…”
Section: Wwwintechopencommentioning
confidence: 93%
“…The pulse energy required will depend on both the material and the chosen application. Machining of a crystal for instance will typically require a much greater energy per pulse, for example energies up to and above 80 Jcm -2 (T. V. Kononenko et al, 2008) for natural diamond, while for index change in PMMA energies above 0.6 Jcm -2 (A. Baum et al, 2007) cause permanent change.…”
Section: Types Of Femtosecond Lasermentioning
confidence: 99%
“…Hence, for this study the focus was on surface patterning. The fs laser pulse energy and writing speed can be determined according to previous research on fs laser microstructuring in the bulk of diamond or diamondlike carbon films [18,19]. Preuss and Stuke [20] found that the ablation threshold of diamond was around 0.6 J/cm 2 for 500 fs laser pulses at a wavelength of 248 nm.…”
Section: Introductionmentioning
confidence: 99%